PERAN MUSLIM DALAM KONFLIK GEOPOLITIK: ANALISIS PERANG ISRAEL-PALESTINA - Syulizar Andien, Hersa; Delia, Ananda; Anisa Khotimah, Farida; Arissaputra, Restu; Parhan, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Israeli-Palestinian conflict, which began in the early 20th century, is a longstanding and complex geopolitical issue characterized by conflict, occupation, and the struggle for self-determination. These conflicts are triggered by historical, religious, and territorial disputes, and involve a wide range of actors, including states, religious groups, and international organizations. This conflict has displaced millions of Palestinians, as Israel undertakes settlement construction in the occupied Palestinian territories. The conflict has significant implications for the geopolitical landscape in the region and has been a source of instability for decades. This article examines the roots of conflict, the geopolitical dynamics that influence it, and its impact on the region and the world. The main focus is on the wars that have taken place, including the causes, consequences, and peace efforts that have been made. Taking into account the external and internal factors influencing this conflict, this article aims to provide a deeper understanding of the Israeli-Palestinian conflict and its relevance in the global geo-political context.